The seismogenic thickness in Italy: constraints on potential magnitude and seismic hazard. (27th September 2016) - Chiarabba, Claudio; De Gori, Pasquale
Abstract: The thickness of the seismogenic layer is a key parameter for seismic hazard, since it can be used to constrain the maximum depth of faulting and the potential magnitude. In this study, we compute the seismogenic thickness in the Italian region by defining the lower seismicity cut‐off, using high‐quality hypocentral locations of earthquakes that occurred in the past decade. Along the eastern Alps, the seismogenic thickness is about 12–14 km, laterally homogeneous along the entire south‐verging thrust front. In the Apennines extensional belt, lateral changes in seismogenic thickness are evident, and correlate with changes in the seismic energy released by past earthquakes. The potential magnitude is larger in the southern Apennines where the seismogenic thickness is greater (16–18 km) than in the northern Apennines where it is less (6–10 km) and seismic energy is partially released by the creeping of faults.